The distribution and variability of low‐level cloud in the North Atlantic trades. (18th February 2014) - Nuijens, L.; Serikov, I.; Hirsch, L.; Lonitz, K.; Stevens, B.
<x xml:space="preserve">Abstract</x> In the North Atlantic trades, variations in the distribution of low‐level cloud are rich. Using two years of observations from a remote‐sensing site located on the east coast of Barbados, the vertical distribution of cloud and its contribution to low‐level cloud amount are explored. The vertical distribution of first‐detected cloud‐base heights is marked by a strong peak near the lifting condensation level (LCL) from passive optically thin shallow cumuli. Cloud with a base near this level dominates the total cloud cover with a contribution of about two‐thirds. The other one‐third comes from cloud with its cloud base further aloft at heights > 1 km, such as cumulus edges or stratiform cloud below the trade inversion. Cloud found aloft, regardless of where its base is located, contains more variance, in particular near the inversion and on time‐scales longer than a day. In turn, cloud near the LCL is surprisingly invariant on longer time‐scales, although consistent with existing theories. Because this component does not systematically vary, changes in cloud cover in response to changes in meteorology or climate may be limited to changes in its contribution from cloud aloft.